Monetary Transmission in Brazil : Has the Credit Channel Changed? - Garcia-Escribano, Mercedes (Washington, D.C. : International Monetary Fund, 2013)
This paper investigates the transmission of monetary policy by private banks in Brazil during the recent easing cycle. The analysis presented uses a panel dataset with information on lending by private banks in Brazil and concludes that monetary transmission through lending volumes was not impaired. Instead, the observed diminished lending appears to be related to supply and demand factors, as well as to the rapid expansion of public banks' lending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet